LEARNING MODEL BASED ON PROBLEMS WITH SAINTIFIC APPROACH TO IMPROVE STUDENTS’ HIGHER ORDER THINKING SKILLS - Lala Jelita Ananda; Elvi Mailani (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2018)
This study aims to determine the ability of Elementary School Teacher Education students’ in mastering Higher Order Thinking Skills with Problem-Based Learning Model (PBM) which used to support Higher Order Thinking Skills problem-oriented situation. The method used in this research is the experimental method. Experiments were used to identify Higher Order Thinking Skills through the application of Problem-Based Learning Model (PBL) with scientific approach to Elementary School Teacher Education students’, Faculty of Education, State University of Medan, in the first semester of Study Year 2017/2018. The research design used was Pre-test and Post-test group because the observation was done 2 times before experiment (O1 / pre-test) and after experiment (O2 / post-test). Based on the results obtained, in the control class using the lecture method obtained by the data with the average learning outcomes 79.08 while with the model of Problem Based Learning with the Scientific Approach obtained by the average data learning outcome is 83.03. Based on the data, it is found that  Fcount> Ftable is 6.53> 2.67 then Ho is rejected and it can be concluded that there are significant differences in the implementation of Problem-Based Learning model with scientific approach in increasing Higher Order Thinking Skills. Keywords : Scientific Approach, Skills, Higher Order Thinking